2021
DOI: 10.3389/fphys.2021.763085
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus-Targeting Polymeric Nanocarriers and Their Biomedical Applications in Thrombolytic Therapy

Abstract: Due to the high morbidity and mortality of cardiovascular diseases, there is an urgent need for research on antithrombotic strategies. In view of the short half-life, insufficient drug penetration, poor targeting capabilities, and hemorrhagic side-effects of traditional thrombus treatment methods, the combination of thrombolytic therapy and nanocarriers brought by the development of nanotechnology in recent years may provide effective solutions for these undesirable side-effects caused by insufficient targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 84 publications
0
11
0
Order By: Relevance
“…A thrombus is heterogeneous in composition but mainly composed of fibrin, platelets, red blood cells, and leukocytes. , Thrombosis is reported to be one of the leading causes of death worldwide, accounting for one in four deaths. , A thrombus can be dissolved by tissue plasminogen activator (tPA) and urokinase plasminogen activator, and the rate of thrombus formation can be reduced with the help of various antiplatelet agents and anticoagulant agents. , However, these agents suffer from several drawbacks such as a short half-life, narrow therapeutic window, and unwanted hemorrhage in tissues. In this regard, there has been increasing interest in the development of nanomaterial-based drug delivery systems that effectively and specifically deliver sufficient antithrombotic agents to the thrombosed vessel, while minimizing their side effects. ,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A thrombus is heterogeneous in composition but mainly composed of fibrin, platelets, red blood cells, and leukocytes. , Thrombosis is reported to be one of the leading causes of death worldwide, accounting for one in four deaths. , A thrombus can be dissolved by tissue plasminogen activator (tPA) and urokinase plasminogen activator, and the rate of thrombus formation can be reduced with the help of various antiplatelet agents and anticoagulant agents. , However, these agents suffer from several drawbacks such as a short half-life, narrow therapeutic window, and unwanted hemorrhage in tissues. In this regard, there has been increasing interest in the development of nanomaterial-based drug delivery systems that effectively and specifically deliver sufficient antithrombotic agents to the thrombosed vessel, while minimizing their side effects. ,, …”
Section: Introductionmentioning
confidence: 99%
“…In this regard, there has been increasing interest in the development of nanomaterial-based drug delivery systems that effectively and specifically deliver sufficient antithrombotic agents to the thrombosed vessel, while minimizing their side effects. 6,8,9 atRA is an active derivative of retinol, a fat-soluble vitamin in the vitamin A family that is critical for normal cellular growth, differentiation, and death. 10,11 atRA is known to have potent antioxidant activity owing to its ability to scavenge reactive oxygen species (ROS) such as hydroxyl radical, superoxide, and nitric oxide.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] To date, a variety of fibrinolytic enzyme delivery systems have attempted to solve the above challenges. [17][18][19][20][21][22][23] For example, Jin et al [24] and Berger et al [25] reported a PEGylated delivery system by direct conjugation of lumbrokinase (LK) and tPA enzymes, respectively, with polyethylene glycol (PEG) to prolong the circulation half-life. Absar et al demonstrated a camouflaged tPA delivery system by conjugating tPA with human serum albumin followed by surface decoration with a thrombus-homing peptide (CQQHHLGGAKQAGDV) for thrombus-targeted delivery of tPA.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a variety of fibrinolytic enzyme delivery systems have attempted to solve the above challenges. [ 17–23 ] For example, Jin et al. [ 24 ] and Berger et al.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, despite their potent antithrombotic actions, the clinical use of antithrombotic drugs such as tissue plasminogen activator is limited by their shortcomings such as high risk of undesirable bleeding complications, short-half-life in circulation, and lack of thrombus targeting ability. 4 In this regard, the concept of targeted delivery systems and stimulus-responsive nanoprodrugs have been exploited to develop strategies to maximize the therapeutic efficacy of antithrombotic agents and minimize their adverse side effects. 5 atRA is a physiologically active metabolite of retinol, a family of vitamin A.…”
mentioning
confidence: 99%